Determinants of re‐compensation in patients with hepatitis B virus‐related decompensated cirrhosis starting antiviral therapy. Issue 1 (18th October 2021) - Kim, Tae Hyung; Um, Soon Ho; Lee, Young‐Sun; Yim, Sun Young; Jung, Young Kul; Seo, Yeon Seok; Kim, Ji Hoon; An, Hyunggin; Yim, Hyung Joon; Yeon, Jong Eun; Byun, Kwan Soo
Summary: Background: Despite antiviral therapy, liver function often fails to recover in patients with hepatitis B virus (HBV)‐related decompensated cirrhosis. Aim: To establish a prognostic model to predict re‐compensation in patients starting potent nucleos(t)ide analogue (NUC) therapy Methods: We analysed 311 consecutive patients with HBV‐related decompensated cirrhosis treated with entecavir or tenofovir. The primary outcome was re‐compensation, defined as recovery to a Child–Pugh score of 5. The BC2AID score was developed from a cohort of 152 subjects based on competing risk models and validated in another cohort of 159 subjects. Results: Re‐compensation occurred in 57.2% and 66.7% of the subjects in the derivation and validation cohorts, respectively. Six independent predictors for re‐compensation were identified in the derivation cohort and these comprised the BC2AID score: bilirubin ≤5 mg/dL (adjusted sub‐distribution hazard ratio [aSHR] 2.18), absence of severe complications (aSHR 2.78), alpha‐fetoprotein (AFP) ≥50 ng/mL (aSHR 2.54), alanine aminotransferase ≥200 IU/L (aSHR 2.62), international normalised ratio ≤1.5 (aSHR 2.37) and ≤6 months from initial decompensation until initiation of NUCs (aSHR 4.79). In the validation cohort, the area under the receiver operating characteristic curve of the BC2AID score for re‐compensation within 1 year of NUC therapy was significantly higher than that of the Child–Pugh, MELD, MELDNa and BE3A scores (0.813 vs 0.691, 0.638, 0.645 and 0.624, respectively; all P < 0.05). Conclusions: Six clinical parameters, including AFP and the timing of antiviral therapy, were combined into a scoring system to accurately predict early re‐compensation in patients with HBV‐related decompensated cirrhosis. Abstract : The new model consisting of six factors was established to predict re‐compensation of patients with HBV‐related decompensated cirrhosis. It stratified the survival and re‐compensation well.